Farmers risk-balancing, consumption and optimal debt level - Esguerra, Almira Jazmin P. (Animo Repository, 2009)
This paper presents a stochastic optimal control/dynamic programming (SOC/DP) approach to derive the optimal debt level and consumption in farm models concerning two sources of undertainty: the return on assets and real interest rate. The SOC/DP analytic framework is used to analyze the impact of risk-reducing farm policies on farms financial and risk adjustments. The results show a violation of the risk-balancing concept, which theorizes that risk-reducing farm policies may lead to increases in financial leverage, total risk, and the expected returns. Also, this study examines the extent to which the estimates of the optimal debt level are biased when interest rate risk is ignored.